Pastoral Literature in Balinese Landscape of Indonesian Poetry Dongeng dari Utara - Hardiningtyas, Puji Retno (International Journal of Psychosocial Rehabilitation, 2020)
This article is very important for analyzing the text of the poem Dongeng dari Utara by focusing on the landscape of people’s lives and the symbolization of nature in Bali. The text of Indonesian poetry Dongeng dari Utara contains a great potential as an ecological literary text because it chooses environmental themes as the ethical orientation of the text. Made Adnyana Ole’s Dongeng dari Utara contains the great potential of ecological literary texts because of the emerge of environmental themes as the ethical orientation of texts. The formulation problem of this research is focused on describing arcadia (way/place of life); bucolic (shepherd); as well as retreat and return discourse in the Dongeng dari Utara. Data collecting used literature study method with note taking technique. Data were analyzed by descriptive analytic methods with interpretive techniques. The eco-criticism theory is used in this research. The results and discussion of this study indicate that the pastoral aesthetic in the poems of Made Adnyana Ole is influenced by the views of the farming community. The rural setting, rice fields, land and natural scenery in a quiet place is one of the pastoral aesthetic models in Dongeng dari Utara poetry. The ideal picture of life in the countryside is described by the characteristics of (a) a quiet, static and static rural nature, (b) human relations and rural nature, (c) a nature that describes the peace, intimacy and simplicity of the countryside, (d) beautiful and harmonious natural rural landscape, (e) attitudes and overseas life and return to nature, (f) attitudes that remember the past, history, and ancestors. Thus, the pastoral aesthetics in the anthology of Dongeng dari Utara poetry is a representation of the attitude of human respect for the cosmic environment in Bali.